2017
DOI: 10.1155/2017/6761719
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Process for Antidiabetic and Antioxidant Activities of Kursi Wufarikun Ziyabit Using Response Surface Methodology and Quantitative Analysis of Main Components

Abstract: By using extraction yield, total polyphenolic content, antidiabetic activities (PTP-1B and α-glycosidase), and antioxidant activity (ABTS and DPPH) as indicated markers, the extraction conditions of the prescription Kursi Wufarikun Ziyabit (KWZ) were optimized by response surface methodology (RSM). Independent variables were ethanol concentration, extraction temperature, solid-to-solvent ratio, and extraction time. The result of RSM analysis showed that the four variables investigated have a significant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…As shown in Figure 3(a), XO inhibitory activity Evidence-Based Complementary and Alternative Medicine increased when the temperature increased from 50 to 75°C and started to decrease towards 100°C as the extraction time decreased. is was in agreement with Edirs et al [46] where the antidiabetic activity of Kursi Wufarikun Ziyabit using protein tyrosine phosphatase-1B and α-glucosidase inhibition assays increased as the extraction temperature increased from 70 to 75°C and 65 to 70°C, respectively. is explains that an increase in the extraction temperature beyond certain value will denature or decompose some of the valuable compounds responsible for inhibiting XO activity [47].…”
Section: Effect Of Extraction Parameters On Xo Inhibitory Activitysupporting
confidence: 92%
“…As shown in Figure 3(a), XO inhibitory activity Evidence-Based Complementary and Alternative Medicine increased when the temperature increased from 50 to 75°C and started to decrease towards 100°C as the extraction time decreased. is was in agreement with Edirs et al [46] where the antidiabetic activity of Kursi Wufarikun Ziyabit using protein tyrosine phosphatase-1B and α-glucosidase inhibition assays increased as the extraction temperature increased from 70 to 75°C and 65 to 70°C, respectively. is explains that an increase in the extraction temperature beyond certain value will denature or decompose some of the valuable compounds responsible for inhibiting XO activity [47].…”
Section: Effect Of Extraction Parameters On Xo Inhibitory Activitysupporting
confidence: 92%
“…Then, our results demonstrated that KWZ successfully induced the HK, which is consistent with the increase of insulin signaling activity. KWZ is rich in antioxidant components, and the previous study gave evidence of the antioxidant activity of the effective part [ 21 ]. Diabetes is related to oxidative stress, marked by increased production of free radicals or impaired antioxidant defenses [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Voucher specimens (Barcode: G. collinum WY01053, H. Scabrum WY01054) were deposited at the Herbarium of the Key Laboratory of Plant Resources and Chemistry of Arid Zone, Xinjiang Technical Institute of Physics and Chemistry, Chinese Academy of Sciences. e KWZ (the roots of G. collinum and aerial parts of H. Scabrum were mixed with the ratio of 7 : 3) were prepared according to the article [21]. e dried matter after preparation was powdered, weighed, and packed in zip pack bags, stored at 4°C for further study.…”
Section: Preparation Of Kwz For Animal Experimentationmentioning
confidence: 99%
See 2 more Smart Citations